Proteins Associated with Persistent Apical Periodontitis: A Scoping Review - Rodrigues da silva, Weslay; Paula Veras Sobral, Ana; Romeiro, Kaline; Lima, Cleiton Rone dos Santos; Isaltino, Marina da Cunha; Telles, Christianne Tavares Velozo; Albuquerque, Diana Santana de (Iranian Endodontic Journal, 2024)
This scoping review aimed to assess immunohistochemical markers associated with the physiopathogenesis of Persistent Apical Periodontitis. The protocol was adapted from the Joanna Briggs Institute Reviewer's Manual (2017) and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines for Scoping Reviews. A total of 239 articles were considered potentially eligible, and their full texts read by two reviewers. Six articles were included. The included articles were published between 1999 and 2017. A total of 12 biomarkers were identified, forkhead box P3, cluster of differentiation (CD)3, CD8, CD450, CD68, transforming growth factor alpha, transforming growth factor-beta1, matrix metalloproteinase-9, receptor activator of nuclear factor kappa beta ligand, osteoprotegerin, CD90 and sex-determining region Y-box 2; categorized according to their applicability. Among the biomarkers identified, receptor activator of nuclear factor kappa beta ligand and osteoprotegerinare were related to bone remodeling in apical periodontitis and may also be associated with persistent apical periodontitis.